Imaging strategies to interpret 3-D noisy audio-magnetotelluric data acquired in Gyeongju, South Korea: data processing and inversion. Issue 2 (8th January 2021) - Uhm, Janghwan; Heo, Junyeong; Min, Dong-Joo; Oh, Seokhoon; Chung, Ho-Joon
SUMMARY: The largest earthquake recorded in South Korea occurred in Gyeongju on 2016 September 12. Since then, understanding the geological structures near the Gyeongju earthquake's epicentre has been demanded. As a preliminary step to understand the geological structures around the epicentre, a 3-D audio-magnetotelluric (AMT) survey was conducted. These 3-D AMT data were imaged through data processing and inversion. However, because the AMT data acquired in Gyeongju were very noisy, conventional imaging procedures did not yield reliable results. To obtain a reliable model inverted from such noisy data, we propose various imaging strategies: an additional data processing technique using the Nyquist diagram after conventional data processing and several inversion strategies related to the selection of data, the weighting of the data, the constraints on the model parameter vector and the Lagrange multiplier used for the regularization. By applying the additional data processing step and several inversion strategies, we were able to successfully invert the noisy field data. The inversion results verify that the data-screening procedure applying the Nyquist diagram remarkably improves the results compared with those obtained using only conventional data processing. The imaging strategies proposed in this case study can be used to image noisy MT/AMT field data for other regions.